Parallel and Distributed Processing Support for a Geospatial Data Visualization DSL - Ewald, Endrius; Vogel, Adriano; Rista, Cassiano; Griebler, Dalvan; Manssour, Isabel; Fernandes, Luiz Gustavo (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2018)
The amount of data generated worldwide related to geolocalization has exponentially increased. However, the fast processing of this amount of data is a challenge from the programming perspective, and many available solutions require learning a variety of tools and programming languages. This paper introduces the support for parallel and distributed processing in a DSL for Geospatial Data Visualization to speed up the data pre-processing phase. The results have shown the MPI version with dynamic data distribution performing better under medium and large data set files, while MPI-I/O version achieved the best performance with small data set files.